2019
DOI: 10.2131/jts.44.167
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV protects against cisplatin-induced liver and kidney injury via autophagy-mediated inhibition of NLRP3 in rats

Abstract: The aim of this study was to explore the role of the NOD-like receptor family, pyrin domain containing (NLRP3) inflammasome and autophagy in Astragaloside IV (AS IV)-mediated protection against cisplatin-induced liver and kidney injury in rats. Rats were intraperitoneally administered cisplatin at a dose of 15 mg/kg and orally administered AS IV for 7 days. Histopathological and biochemical analysis were used to assess liver and kidney function. The levels and localization of NLRP3 and autophagy-associated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…Moreover, Astragaloside IV could further enhance autophagy by increasing the LC3II/LC3I ratio and inhibiting the pP62 expression. Liu [55], Wang [56] and Qu [57] confirmed that Astragaloside IV could activate autophagy in human degenerative chondrocytes and renal disease, respectively. We found that Astragaloside IV can activate autophagy in HT22 cells after OGD/R, it is consistent with the results of the above studies [55,56,57] about the effects of Astragaloside IV on autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Astragaloside IV could further enhance autophagy by increasing the LC3II/LC3I ratio and inhibiting the pP62 expression. Liu [55], Wang [56] and Qu [57] confirmed that Astragaloside IV could activate autophagy in human degenerative chondrocytes and renal disease, respectively. We found that Astragaloside IV can activate autophagy in HT22 cells after OGD/R, it is consistent with the results of the above studies [55,56,57] about the effects of Astragaloside IV on autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…However, SIRT3 can protect from the AKI caused by cisplatin by inducing autophagy (Zhao et al, 2018). Moreover, Astragaloside IV can protect from cisplatin-induced kidney injury by inducing the autophagy and suppressing the NF-kB signal pathway, thereby down-regulating the expression of NLRP3 inflammasome (Qu et al, 2019). Moreover, the caspase inhibition can reduce the production of caspase-1 and IL-1β, and thus protect from the cisplatin-induced kidney injury (Lee et al, 2015).…”
Section: Inflammasomes In Acute Kidney Injurymentioning
confidence: 99%
“…Although cisplatin (CP) [ cis -diamminedichloroplatinum (II), CDDP], is potent anticancer medication use to treat a variety of tumors including testicular, ovarian, bladder, and lung ( Ibrahim et al., 2016 ; Karwasra et al., 2016 ). Several recent studies recorded that the CP induces hepatotoxicity ( Abdellatief et al., 2017 ; Qu et al., 2019 ; Abdel-Daim et al., 2020 ; Hwang et al., 2020 ) and nephrotoxicity ( Abdel-Daim et al., 2017 ; Abdel-Razek et al., 2020 ; Abo-Elmaaty et al., 2020 ; Sadeghi et al., 2020 ). Miller et al.…”
Section: Introductionmentioning
confidence: 99%